Correction: Brucellosis Seropositivity in Animals and Humans in Ethiopia: A Meta-analysis. - Getachew Tadesse (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0005006.].